Agricultural Expansion-Induced Infiltration Rate Change in a West African Tropical Catchment - Yacouba Yira; Aymar Y. Bossa (Applied and Environmental Soil Science)
Land use and land cover in the Dano catchment is characterized by a rapid conversion from seminatural vegetation (fallow) to agriculture (cropland). The study compares both the saturated (Ks) and the unsaturated (Kh) hydraulic conductivities under cropland and fallow in the catchment to gain insights into the effect of the current land use on soil water dynamics. Hydraulic conductivity was measured under forty-two (42) pairs of adjacent cropland-fallow plots using a Hood infiltrometer. Ks, Kh, bulk density, and soil texture were further compared using a paired two-tailed Student’s t-test (p=0.05). The results showed that both Ks and Kh are highly variable irrespective of the land use type (coefficient of variation > 100%). The results also showed that Ks was significantly higher (1.16-fold on average) under fallow compared to cropland. As for Kh, the results showed that, from −2 cm to zero tension heads (h), Kh under cropland and fallow is not significantly different; however, as the supplied tension decreases up to the saturation state, Kh under fallow becomes statistically higher compared to cropland. No significant difference was found between soil textures and bulk density under cropland and fallow meaning that the observed differences of Ks and Kh under cropland and fallow were caused by land use and not preexisting difference in texture. These results suggest an increasing risk of erosion, soil fertility reduction, and flood in the catchment because of agricultural land expansion.